Biological control of the tick Amblyomma sculptum (Acari: Ixodidae) using the fungus Purpureocillium lilacinum alone and in association with the fungus Metarhizium anisopliae - Thais Araújo Moura; Isabella Barboza de Almeida; Elianai Ribeiro de Souza; Fernanda Calvo Duarte; Hamilton Humberto Ramos; Matheus de Oliveira Araújo; João Ricardo Sato; José Eduardo Marcondes de Almeida; Márcia Cristina Mendes (Biological Control)
The tick Amblyomma sculptum is of major public health interest given that it transmits the bacterium Rickettsia rickettsii, the pathogen that causes Brazilian spotted fever. Capybaras are primary hosts for this ectoparasite species and natural reservoirs for this bacterium. With the aim of finding new means for controlling this tick, the objective of this study was to evaluate the efficacy of the fungus Purpureocillium lilacinum (IBCB 130) alone and in association with the fungus Metarhizium anisopliae (IBCB 425), in the field. Two areas of 5000 m2 (Pl and MaPl) were used for applications of aqueous suspensions of fungus, once a month over an 11-month period, and there was also a control area that did not receive any application. The fungus P. lilacinum was applied in the area Pl at a concentration of 6 x 1011 conidia/ha; and an association of the two fungi (3 x 1011 conidia/ha for P. lilacinum and 1 x 1013 conidia/ha for M. anisopliae) was applied in the area MaPl. One week after each application, ticks were collected by means of CO2 attraction traps that were laid out on the vegetation. The total number of ticks in each trap was then counted and up to 16 individuals (adults and nymphs) from each area were separated out and distributed individually and in pools. These were kept in climate-controlled chambers at 28 °C and 80 % relative humidity. On days 5, 10 and 15, mortality among the ticks (individually and in pools) was assessed. Fisher’s exact test was used in statistical analysis to ascertain the reduction in population in the treated areas, using data from each area according to periods when either nymphs or adults of A. sculptum predominated (epoch, Ep) or there was no predominance (non-epoch, NEp). The mortality analysis on adult ticks that were housed individually showed percentages of 46 % for area Pl, 44 % for area MaPl and 31 % for the control area, in the evaluation of the 15th day. For the pooled adults, the percentage mortality was 55 % for Pl, 31 % for MaPl and 25 % for the control. The percentage reduction in population for ticks in the adult phase was 69 % for Pl, 69.6 % for MaPl and 7.4 % for the control. For nymphs housed individually, the 15th day mortality was 68 % for Pl, 58 % for MaPl and 60 % for the control; while for the nymphs in pools, the percentages were 92 %, 93 % and 35 % for Pl, MaPl and control, respectively. These results indicate that the areas over which the fungus P. lilacinum was applied presented considerable reductions in population through both treatments, with a lower dosage of fungus in the application of Pl alone than in the application of MaPl. In the light of the results obtained, this study suggests that use of the fungus P. lilacinum forms an effective alternative for biological control of A. sculptum.